2017
DOI: 10.1186/s13643-017-0600-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating progestogens for prevention of preterm birth international collaborative (EPPPIC) individual participant data (IPD) meta-analysis: protocol

Abstract: BackgroundPreterm birth is the most common cause of death and harm to newborn babies. Babies that are born early may have difficulties at birth and experience health problems during early childhood. Despite extensive study, there is still uncertainty about the effectiveness of progestogen (medications that are similar to the natural hormone progesterone) in preventing or delaying preterm birth, and in improving birth outcomes. The Evaluating Progestogen for Prevention of Preterm birth International Collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…18 How best to adjudicate the findings of the PROLONG trial, given it was underpowered and inconclusive regarding assessment of treatment efficacy, will be challenging for clinicians, patients, and policy makers. Combining data in systematic reviews and/or meta-analyses 19,20 to attempt to differentiate a population with the most optimal benefit/risk ratio will be important. The absence of other evidence-based interventions to offer this orphan population (women with prior SPTB) combined with the reality that 17-OHPC has been widely used for over 15 years adds to the complexity.…”
Section: Resultsmentioning
confidence: 99%
“…18 How best to adjudicate the findings of the PROLONG trial, given it was underpowered and inconclusive regarding assessment of treatment efficacy, will be challenging for clinicians, patients, and policy makers. Combining data in systematic reviews and/or meta-analyses 19,20 to attempt to differentiate a population with the most optimal benefit/risk ratio will be important. The absence of other evidence-based interventions to offer this orphan population (women with prior SPTB) combined with the reality that 17-OHPC has been widely used for over 15 years adds to the complexity.…”
Section: Resultsmentioning
confidence: 99%
“…Neurodevelopmental impairments are common after preterm birth 41,42 . Even though there is still considerable heterogeneity between progesterone trials, a large recent IPD‐MA showed a reduction of preterm birth after progesterone in singleton pregnancies at high risk for preterm birth 43 . Therefore, we anticipated improvements in neurodevelopmental outcomes among prenatally progesterone exposed children.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Even though there is still considerable heterogeneity between progesterone trials, a large recent IPD-MA showed a reduction of preterm birth after progesterone in singleton pregnancies at high risk for preterm birth. 43 Therefore, we anticipated improvements in neurodevelopmental outcomes among prenatally progesterone exposed children. However, in four 32,34,37,38 of five studies, preterm birth rate was comparable between the progesterone and the placebo group.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Vaginal administration of natural progesterone could be an alternative strategy but the Cochrane review and OPPTIMUM study did not find evidence for reduction in PTB risk with this strategy . It is hoped that soon to be published individual patient data analysis by the EPPPIC group will provide definitive evidence in this respect …”
Section: Discussionmentioning
confidence: 99%